Decadal changes in size, salinity, waterbirds, and fish in lakes of the Konya Closed Basin, Turkey, associated with climate change and increasing water abstraction for agriculture. Issue 4 (2nd October 2021) - Yılmaz, Gültekin; Çolak, Mehmet Arda; Özgencil, İbrahim Kaan and Metin, Melisa and Korkmaz, Mustafa and Ertuğrul, Serhat and Soyluer, Melisa and Bucak, Tuba and Tavşanoğlu, Ülkü Nihan and Özkan, Korhan and Akyürek, Zuhal and Beklioğlu, Meryem and Jeppesen, Erik
ABSTRACT: The Konya Closed Basin (KCB) in Turkey has a cold semiarid to warm Mediterranean climate and hosts the largest Turkish freshwater lake, Lake Beyşehir, and the iconic saline Lake Tuz. Using published as well as our own ground-truth and remote sensing data, we provide (1) a brief description of the paleoenvironmental changes in the KCB; followed by (2) a detailed description of the changes in land use, crop farming, groundwater and surface water levels, and climate; and (3) associated changes in lake water surface area and salinity as well as in waterbird and fish communities during the past 40 years. The KCB is intensively farmed, and the farming of mainly water intensive crops has increased substantially, especially since 2000. This, combined with climate warming, has led to a substantial rate of reduction of the groundwater level (up to 1 m/yr) and the surface area of the lakes and wetlands, followed by an increase in salinisation, and even complete loss of several wetlands. Three globally threatened waterbird species face extinction in the basin, and 18 of the 62 previous breeding species have already been lost. The KCB has 38 fish species, of which 74% are endemic and 61% are considered threatened or near threatened. Modelling projections using various climate and land use scenarios predict serious additional reductions of the water level in the future due to climate change, leading to deterioration (or complete loss) of lake ecosystems and the services they provide.